Positive electrode active material and preparation method thereof, positive plate and battery
By controlling the exposure of (110) surfaces, (100) surfaces and (311) surfaces of nickel-manganate lithium manganate and using rock salt phase generation, the problems of slow lithium ion transmission and manganese dissolution in nickel-manganate lithium batteries have been solved, which has significantly improved the Rate performance and stability.
Patent Information
- Application Number
- CN202411361195.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-14
AI Technical Summary
When lithium nickel manganate is the positive electrode active material of lithium ion batteries, the (111) surface lithium ions transmission rate is slow and manganese dissolution is easy to occur, affecting its rate performance and stability.
By defining the exposure degree of (110) plane, (100) plane and (311) crystal plane, combined with the formation of lithogenic salt phase, the lithium ion conduction rate is improved and manganese dissolution is reduced, a specific chemical composition and preparation method is used to prepare the positive electrode active material.
It significantly improves the rate performance and cycle stability of nickel-manganate lithium battery, enhances the lithium ion conduction rate, and reduces manganese dissolution phenomenon.
Smart Images

Figure CN119315025A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium nickel manganese oxide is a lithium-ion battery positive electrode active material with a spinel structure. Compared with other spinel structured positive electrode active materials (such as lithium manganese oxide and lithium iron phosphate), lithium nickel manganese oxide has a higher operating voltage and energy density. Therefore, it has broad application prospects in electric vehicles, energy storage systems, and portable electronic devices.
[0003] Common lithium nickel manganese oxide materials are typical octahedral morphologies of spinel materials, usually with the (111) face exposed to form an octahedral morphology. However, the lithium ion transmission rate of the (111) face is slow and manganese is easily dissolved, which is not conducive to the rate performance and stability of lithium nickel manganese oxide as a positive electrode active material. Therefore, how to control the exposure degree of other crystal faces of lithium nickel manganese oxide to improve the rate performance and stability of lithium nickel manganese oxide batteries is an urgent problem to be solved. Summary of the invention
[0004] The present invention provides a positive electrode active material, which can significantly improve the rate performance and cycle stability of a corresponding battery by limiting the exposure degree of a specific crystal face.
[0005] The present invention also provides a method for preparing the positive electrode active material. The method can prepare the positive electrode active material and has a simple process.
[0006] The present invention also provides a positive electrode sheet. Since the positive electrode sheet includes the positive electrode active material, it has the advantages of fast ion transmission rate and good stability.
[0007] The present invention also provides a battery. Since the battery includes the positive electrode sheet, the battery has both high rate performance and cycle stability.
[0008] In a first aspect, the present invention provides a positive electrode active material, wherein the positive electrode active material satisfies the following formula 1:
[0009] I1+I2+I3≤10.20 Formula 1;
[0010] Among them, I1 is I(111) / I(311) in the XRD spectrum of the positive electrode active material, I2 is I(111) / I(400) in the XRD spectrum of the positive electrode active material, I3 is I(111) / I(440) in the XRD spectrum of the positive electrode active material, and I1, I2, and I3 are all not 0.
[0011] Furthermore, the XRD spectrum of the positive electrode active material also includes rock salt phase Li x Ni 1-x The diffraction peak of O.
[0012] Furthermore, the chemical composition of the positive electrode active material includes Li 1+x Ni 0.5+y Mn 1.5+z M u N v O w , wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 0<v≤0.03, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F; N includes at least one of Mg, Ca, Co, Ni, Zn, Sr, Y, Sn, Ba, La, Ce, and Nd.
[0013] Furthermore, the positive electrode active material satisfies the following formula 2:
[0014] 0.0005≤y / x≤0.0100 Formula 2;
[0015] Wherein, x is the particle size of the positive electrode active material, in μm, and y is the thickness extending from the surface of the positive electrode active material to the core to the point where the N concentration is 0, in μm.
[0016] Further, 0.001 μm≤y≤0.020 μm.
[0017] And / or, the Dv50 of the positive electrode active material is 1 to 15 μm.
[0018] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:
[0019] 1) Prepare a first precursor material, wherein the chemical composition of the first precursor material is Li 1+x Ni 0.5+y Mn 1.5+z M u O w , wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F;
[0020] 2) mixing the first precursor material with a soluble salt solution of N, stirring, filtering, and drying in sequence to obtain a second precursor material;
[0021] 3) The second precursor material is sintered at 700-1000° C. to obtain the positive electrode active material.
[0022] Further, the first precursor material is prepared by a method comprising the following process:
[0023] The molecular formula is Ni 0.5 Mn 1.5 The (OH)4 precursor, lithium source and M source are mixed, and the obtained mixture is sintered at 900-1100°C for 5-30h, and then cooled to 600-800°C at a cooling rate of 0.1-3°C / min, and kept warm for 1-10h to obtain the first precursor material.
[0024] Furthermore, in the N soluble salt solution, the concentration of element N is 0.01 to 1 mol / L.
[0025] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material as described in the first aspect.
[0026] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the third aspect.
[0027] The positive electrode active material provided by the present invention defines the exposure degree of the (110) plane, (100) plane and (311) plane by formula 1, which can improve its lithium ion conduction rate and reduce manganese dissolution, thereby significantly improving the rate performance and cycle stability of the corresponding battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0029] Figure 1 is a SEM image of the positive electrode active material of Example 1;
[0030] Figure 2 is a SEM image of the positive electrode active material of Example 2;
[0031] Figure 3 is a SEM image of the positive electrode active material of Comparative Example 1;
[0032] Figure 4 1 is a XRD comparison diagram of the positive electrode active materials of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0034] In order to expose other crystal planes other than the (111) crystal plane of lithium nickel manganese oxide, thereby improving the rate performance and stability of the battery, the present invention adopts the following technical solutions:
[0035] In a first aspect, the present invention provides a positive electrode active material, wherein the positive electrode active material satisfies the following formula 1:
[0036] I1+I2+I3≤10.20 Formula 1;
[0037] Among them, I1 is I(111) / I(311) in the XRD spectrum of the positive electrode active material, I2 is I(111) / I(400) in the XRD spectrum of the positive electrode active material, I3 is I(111) / I(440) in the XRD spectrum of the positive electrode active material, and I1, I2, and I3 are all not 0.
[0038] It should be noted that in Formula 1, I(111) refers to the diffraction peak intensity of the (111) crystal plane in the XRD spectrum of the positive electrode active material, and its intensity is measured by the height of the diffraction peak. Further, I(111) / I(311) refers to the ratio of the diffraction peak intensity of the (111) crystal plane to the diffraction peak intensity of the (311) crystal plane in the XRD spectrum of the positive electrode active material, and the same applies to I(111) / I(400) and I(111) / I(440).
[0039] In the present invention, the total exposure of the (440) plane, (400) plane and (311) plane relative to the (111) crystal plane can be defined by formula 1, which helps to improve the rate performance and stability of the positive electrode material. The reason is that different crystal planes of the positive electrode active material have different atomic arrangements and surface characteristics. Therefore, the exposure of different crystal planes has different effects on the electrochemical properties of the positive electrode active material. In detail, affected by the surface energy, lithium nickel manganese oxide tends to form a regular octahedral morphology to expose the (111) plane to reduce the surface energy. However, the lithium ion transmission of the (111) plane is slow and easily leads to Mn dissolution. The (110) plane is aligned with the lithium ion transmission direction (8a-16C-8a), and the (100) plane and the (110) plane have higher lithium ion density, so the (100) plane and the (110) plane have faster ion transmission speed. The present invention can improve the rate performance and cycle stability of lithium nickel manganese oxide by controlling the exposure ratio of the (110) plane, the (100) plane and the (311) crystal plane, thereby meeting the needs of different application scenarios. In addition, in the XRD spectrum, since the (110) and (100) planes are low-index crystal planes and are at a lower 2-Theta angle, they are difficult to identify. The (440) and (400) planes are parallel to the (100) and (100) planes. Therefore, the present invention selects (440) and (400) to replace (100) and (100) for limitation, which also shows the reduction of the (111) plane in the material system from the side.
[0040] In a specific embodiment, 7≤I1+I2+I3≤10.20, 7.5≤I1+I2+I3≤10.20, 8≤I1+I2+I3≤10.
[0041] In an optional embodiment, the XRD spectrum of the positive electrode active material also includes a rock salt phase Li x Ni 1-x The formation of the rock salt phase is beneficial to passivating the surface of lithium nickel manganese oxide, further reducing the surface oxidation of lithium nickel manganese oxide, reducing surface side reactions, and hindering the dissolution of Mn, thereby further improving the cycle stability of the positive electrode active material.
[0042] In one embodiment, the rock salt phase Li x Ni 1-x The diffraction peaks of O correspond to 2θ of 37.5° and 43.5°.
[0043] In an alternative embodiment, the chemical composition of the positive electrode active material includes Li 1+x Ni 0.5+y Mn 1.5+ z M u N v O w, wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 0<v≤0.03, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F; N includes at least one of Mg, Ca, Co, Ni, Zn, Sr, Y, Sn, Ba, La, Ce, and Nd.
[0044] In an alternative embodiment, the positive electrode active material satisfies the following formula 2:
[0045] 0.0005≤y / x≤0.0100 Formula 2;
[0046] Wherein, x is the particle size of the positive electrode active material, in μm, and y is the thickness extending from the surface of the positive electrode active material to the core to the point where the N concentration is 0, in μm.
[0047] In the above embodiment, N only exists on the surface within a specific thickness range of the positive electrode active material, and the surface can be understood as a surface reconstruction shell layer, while the interior relative to the surface reconstruction shell layer does not contain element N, which can be understood as an inner core relative to the surface reconstruction shell layer. The surface reconstruction shell layer is the main factor in regulating the positive electrode active material to satisfy Formula 1.
[0048] The particle size x of the above-mentioned positive electrode active material refers to the specific particle size value of a single positive electrode active material, which can be obtained by SEM measurement. The thickness y of the above-mentioned positive electrode active material in the direction from the surface to the core can be obtained by linear scanning EDS measurement of the cross-section of a high-precision transmission electron microscope.
[0049] In a specific embodiment, 1 nm≤y≤20 nm.
[0050] In an optional embodiment, the Dv50 of the positive electrode active material is 1 to 15 μm. Exemplarily, the Dv50 of the positive electrode active material is 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm or a range consisting of any two thereof.
[0051] The above Dv50 represents the particle size value corresponding to 50% (by volume) of the cumulative amount in the particle size cumulative distribution curve, which is generally obtained by testing with a laser diffraction particle size distribution instrument.
[0052] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:
[0053] 1) Prepare a first precursor material, wherein the chemical composition of the first precursor material is Li 1+x Ni 0.5+y Mn 1.5+z M u O w , wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F;
[0054] 2) mixing the first precursor material with a soluble salt solution of N, stirring, filtering, and drying in sequence to obtain a second precursor material;
[0055] 3) The second precursor material is sintered at 700-1000° C. to obtain the positive electrode active material.
[0056] In the above preparation method, after the first precursor material and the soluble salt solution of N are mixed and stirred, a small amount of N salt is uniformly retained on the surface of the first precursor material after washing and drying, and then the N ions induce the surface reconstruction of the first precursor material through secondary sintering, so that it exposes more (110) faces, (100) faces and (311) faces other than the (111) crystal face. These crystal faces help to improve the rate performance and stability of lithium nickel manganese oxide. Secondly, the N element is an element with low oxidizing property and is not easy to increase the valence state. These elements can also promote the formation of rock salt phase, which is beneficial to passivate the surface of lithium nickel manganese oxide, reduce the oxidizing property of lithium nickel manganese oxide, and reduce surface side reactions, thereby further improving the stability of lithium nickel manganese oxide.
[0057] Taking N acetate as an example, the above preparation method can promote the formation of (110) and (100) planes and rock salt phases due to the following reasons: N acetate is used to wash lithium nickel manganese oxide, and the acetate in the acetate is acidic after ionization, and H + Li in nickel manganese oxide + Lithium-hydrogen exchange is carried out to elute the lithium ions on the outer surface of lithium nickel manganese oxide into the solution, while the N ions in the acetate solution remain on the outer surface of lithium nickel manganese oxide. Therefore, the outer surface of lithium nickel manganese oxide is in a lithium-poor and transition metal-rich state. In the subsequent sintering process, the surface of lithium nickel manganese oxide, which deviates significantly from the equilibrium state, is reconstructed, thereby exposing more (110) and (100) faces and forming a rock salt phase.
[0058] In some embodiments, when N is Ni, it cannot be detected by a high-precision transmission electron microscope. In this case, the chemical composition of the positive electrode active material and the concentration of N can be inferred based on the chemical composition of the first precursor material during preparation and the total Ni content of the obtained positive electrode active material.
[0059] In some embodiments, the above preparation method can specifically achieve the following effects:
[0060] In the XRD spectrum of the first precursor material, I(111) / I(311) is denoted as T1, I(111) / I(400) is denoted as T2, and I(111) / I(440) is denoted as T3. 1+ T 2+ T3)-(I1+I2+I3)] / (T 1+ T 2+ T3)≥5%.
[0061] The above-mentioned soluble salt solution of N includes but is not limited to acetate, oxalate, citrate, nitrate, etc. of the N element, preferably acetate.
[0062] It should be noted that the first precursor material is a conventional lithium nickel manganese oxide material without a reconstructed shell, which can be purchased commercially or prepared according to conventional methods. In an optional embodiment, the first precursor material is prepared by a method including the following process:
[0063] The molecular formula is Ni 0.5 Mn 1.5 The (OH)4 precursor, lithium source and M source are mixed, and the obtained mixture is sintered at 900-1100°C for 5-30h, and then cooled to 600-800°C at a cooling rate of 0.1-3°C / min, and kept warm for 1-10h to obtain the first precursor material.
[0064] Illustratively, the M source may be a compound of M, preferably an oxide of M.
[0065] In an optional embodiment, the concentration of element N in the soluble salt solution of N is 0.01 to 1 mol / L. If the concentration of element N is too low, the improvement effect is not significant. If the concentration is too high, the reconstruction depth is too large, the internal structure is reconstructed, and the capacity is affected.
[0066] More preferably, in the N soluble salt solution, the concentration of element N is 0.01 to 0.2 mol / L. For example, the concentration of element N is 0.05 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L or any two thereof.
[0067] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a positive electrode active layer disposed on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material as described in the first aspect.
[0068] It can be understood that the positive electrode active layer also includes a conductive agent and a binder.
[0069] Exemplarily, the material of the above-mentioned current collector is not specifically limited in the present invention. For example, it can be selected from any one or more of copper foil, titanium foil, tin foil, chromium foil and composite foils of the above metals; the conductive agent can be any well-known carbon material with conductive properties, for example: it can be at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.
[0070] The thickness, surface density and thickness of the positive electrode active material layer of the positive electrode sheet are not specifically limited in the present invention. However, in order to balance the battery capacity, cycle life and energy density, in a specific embodiment, the thickness of the positive electrode sheet is 40-120 μm, including but not limited to: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc.; the surface density of the positive electrode sheet is 3-10 mg / cm 2 , including but not limited to: 3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm 2 、6.5mg / cm 2 , 7mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 etc.; the thickness of the positive electrode active material layer is 20-60 μm, specifically including but not limited to: 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, etc.
[0071] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the third aspect.
[0072] It can be understood that the battery of the present invention may further include a negative electrode sheet, a separator and an electrolyte.
[0073] The present invention does not specifically limit the above-mentioned separator, and any known porous structure separator with electrochemical stability and chemical stability can be selected, for example, it can be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The separator can be a single layer or a multilayer.
[0074] The present invention does not specifically limit the above-mentioned electrolyte, for example, an electrolyte including an organic solvent and an electrolyte salt is selected. Among them, the organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and can be an organic solvent for battery electrolyte known in the art, such as: one or more of fluorinated carbonates, fluorinated carboxylates, non-fluorinated carbonates, fluorinated carbonates, non-fluorinated carboxylates, fluorinated carboxylates, fluorinated carboxylates, fluorinated ethers, non-fluorinated ethers, and tetrahydrofuran; the electrolyte salt is used as a source of ions, and can be an electrolyte salt for battery electrolyte known in the art, such as: one or more of lithium hexafluorophosphate, bistrifluoromethylsulfonyl imide, and bis(fluorosulfonyl)imide lithium.
[0075] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.
[0076] The present invention is further described below in conjunction with specific embodiments:
[0077] Example 1
[0078] This example provides a positive electrode active material C1, whose chemical composition is Li 1.0078 Ni 0.4990 Mn 1.4966 N 0.0044 O 3.9785 , N=Ni, and the positive electrode active material is a single crystal positive electrode active material.
[0079] The preparation method thereof comprises the following steps:
[0080] 1) 2kg precursor Ni 0.5 Mn 1.5 (OH)4 and 415.19g lithium carbonate were added into a high mixer, and the mixture was stirred until uniform. The mixture was sintered at 1050°C for 10h, and then cooled to 700°C at a cooling rate of 0.5°C / min and kept at this temperature for 5h. After natural cooling, the mixture was crushed and sieved to obtain the first precursor material A1.
[0081] 2) The first precursor material is added to a 0.1 mol / L nickel acetate solution with a water-to-material mass ratio of 1:5, stirred at a rate of 500 rpm for 5 min, centrifuged to remove excess nickel acetate aqueous solution after stirring, and dried at 100° C. to obtain a second precursor material coated with nickel acetate;
[0082] 3) The second precursor material was sintered at 900° C. for 10 h and naturally cooled to obtain the positive electrode active material C1.
[0083] Embodiment 2-10
[0084] A positive electrode active material C2-C10 is provided respectively, and the difference between the positive electrode active material C2-C10 and the embodiment 1 is shown in Table 1;
[0085] The preparation method thereof is referred to Example 1.
[0086] Comparative Example 1
[0087] This example provides a positive electrode active material D1, the difference between which and Example 1 is shown in Table 1;
[0088] The preparation method thereof is as described in Example 1, except that only step 1) is performed.
[0089] Comparative Example 2
[0090] This example provides a positive electrode active material D2, the differences between which and Example 1 are shown in Table 1;
[0091] The preparation method thereof is different from that of Example 1 in that:
[0092] 2) The first precursor material A1 was added to deionized water at a water-to-material mass ratio of 1:5, and stirred at a rate of 500 rpm for 5 minutes. The excess water was then removed by centrifugation and dried at 100°C. After drying, the dried material was sintered at 900°C for 10 hours, and the positive electrode active material D2 was obtained after natural cooling.
[0093] Embodiment 11
[0094] A positive electrode active material C11 is provided. The difference between it and Example 1 is shown in Table 1. The preparation method thereof refers to Example 1, except that: Step 1) 2 kg of precursor Ni 0.5 Mn 1.5 (OH)4, 463.54g lithium carbonate and 62.75g ammonium dihydrogen phosphate were added to a high mixer and mixed and stirred until uniform. The mixture was sintered at 1050°C for 10h, then cooled to 700°C at a cooling rate of 0.5°C / min and kept warm for 5h. After natural cooling, it was crushed and sieved to obtain the first precursor material A2; the nickel acetate aqueous solution in step 2) was replaced with the solution shown in Table 1.
[0095] Examples 12-13
[0096] A positive electrode active material C11 is provided respectively, and the difference between it and Example 11 is shown in Table 1; its preparation method refers to Example 11.
[0097] Comparative Example 3
[0098] This example provides a positive electrode active material D3, the differences between which and Example 11 are shown in Table 1;
[0099] The preparation method thereof is similar to that of Example 11, except that only step 1) is performed.
[0100] Embodiment 14
[0101] A positive electrode active material C14 is provided, and the difference between it and Example 1 is shown in Table 1; its preparation method refers to Example 1, except that: Step 1) 2 kg of precursor Ni 0.5 Mn 1.5 (OH)4, 425.66g lithium carbonate and 25.43g Ta2O5 were added to a high-speed mixer and mixed and stirred until uniform. The mixture was sintered at 1050°C for 10h, then cooled to 700°C at a cooling rate of 0.5°C / min and kept warm for 5h. After natural cooling, it was crushed and sieved to obtain the first precursor material A3; the nickel acetate aqueous solution in step 2) was replaced with the solution shown in Table 1.
[0102] Examples 15-16
[0103] A positive electrode active material C15-16 is provided respectively, and the difference between it and Example 14 is shown in Table 1; its preparation method refers to Example 14.
[0104] Comparative Example 4
[0105] This example provides a positive electrode active material D4, the differences between which and Example 14 are shown in Table 1;
[0106] The preparation method thereof is as described in Example 1, except that only step 1) is performed.
[0107] Embodiment 17
[0108] A positive electrode active material C17 is provided. The difference between it and Example 1 is shown in Table 1. The preparation method thereof refers to Example 1, except that: 2 kg of precursor Ni 0.5 Mn 1.5(OH)4, 471.08g lithium carbonate and 63.62g ammonium dihydrogen phosphate, 8.63g Ta2O5, 10.12g Nb2O5, and 8.92g WO3 are added to a high mixer and mixed and stirred until uniform. The mixture is sintered at 1050°C for 10h, then cooled to 700°C at a cooling rate of 0.5°C / min and kept warm for 5h. After natural cooling, it is crushed and sieved to obtain a first precursor material A4; the nickel acetate aqueous solution in step 2) is replaced with the solution shown in Table 1.
[0109] Examples 19-20
[0110] A positive electrode active material C18-20 is provided respectively, and the difference between it and Example 17 is shown in Table 1; its preparation method refers to Example 17.
[0111] Comparative Example 5
[0112] This example provides a positive electrode active material D5, the differences between which and Example 17 are shown in Table 1;
[0113] The preparation method thereof is as described in Example 1, except that only step 1) is performed.
[0114] The following tests were performed on the positive electrode active materials of the above embodiments and comparative examples:
[0115] 1. The microscopic morphology of the positive electrode active materials of the above-mentioned embodiments and comparative examples was observed by SEM, wherein: Figure 1 The SEM image of the positive electrode active material of Example 1 is shown. Figure 2 The SEM image of the positive electrode active material of Example 3 is shown. Figure 3 The SEM image of the positive electrode active material of Comparative Example 1 is shown. Figure 1-3 It can be seen that the octahedral morphology of the lithium nickel manganese oxide positive electrode active material of Examples 1-2 has undergone significant changes, with truncated corners and edges appearing, exposing the (100) and (110) faces, while the lithium nickel manganese oxide positive electrode active material of Comparative Example 1 has a typical octahedral morphology.
[0116] 2. The crystal structures of the positive electrode active material powders of the above-mentioned embodiments and comparative examples were tested by XRD, wherein I(111) / I(311) in the XRD spectrum of the first precursor material was recorded as T1, I(111) / I(400) was recorded as T2, and I(111) / I(440) was recorded as T3, TI=[(T 1+ T 2+ T3)-(I1+I2+I3)] / (T 1+ T 2+ T3)×100%.
[0117] Figure 4The XRD diffraction patterns of Example 1 and Comparative Example 1 show that both Comparative Example 1 and Example 1 meet the requirements of LiNi 0.5 Mn 1.5 The standard diffraction pattern of O4. The curve of comparative example 1 is flat near 2-Theta = 37.6 and 43.6°, and there is no rock salt phase Li x Ni 1-x There is a diffraction peak of O. In Example 1, there is an obvious diffraction peak, which proves that after surface reconstruction, lithium nickel manganese oxide produces rock salt phase Li x Ni 1-x O.
[0118] Some structural parameters and preparation parameters of the positive electrode active materials of the examples and comparative examples are summarized in Table 1;
[0119] Table 1:
[0120]
[0121]
[0122] In the table, “ / ” represents that the result is not recorded. The sintering conditions of the examples only refer to the sintering conditions of step 3), and the sintering conditions of the comparative examples refer to the sintering conditions of step 1).
[0123] Application Example 1
[0124] The positive electrode sheet is prepared using the positive electrode active materials of the above embodiments and comparative examples, comprising the following steps:
[0125] The positive electrode materials of the above examples and comparative examples were added to an appropriate amount of NMP in a ratio of positive electrode material: conductive agent (Super P): binder (PVDF) = 94.5:3:2.5, and mixed and homogenized using a degassing machine. The mixed slurry was coated on aluminum foil to obtain a positive electrode plate, and the surface loading of the positive electrode active material of the plate was 8 mg / cm 2 .
[0126] Application Example 2
[0127] The preparation of a battery using the above-mentioned positive electrode sheet comprises the following steps:
[0128] The button-type half-cell is prepared using the above-mentioned positive electrode sheet, comprising the following steps: punching the positive electrode sheet obtained in Application Example 1 into a plate with a diameter of 15 mm, assembling a CR2430 button-type battery in an argon glove box, and using a metal lithium sheet as the counter electrode.
[0129] Performance Test:
[0130] The following electrical properties of each battery assembled in Application Example 2 were tested separately (results are shown in Table 2):
[0131] Electrochemical performance test: Nominal capacity 150mAh / g, electrochemical window 3.5~4.95V. The capacity test procedure is to charge the assembled button cell at a set rate to 4.95V, then charge at a constant voltage to a current density of 0.05C, and then discharge at a set rate (0.33C, 2C) to 3.5V. The discharge specific capacity obtained is the discharge specific capacity at that rate.
[0132] Mn dissolution test: The prepared lithium nickel manganese oxide positive electrode is used to prepare a full battery, the negative electrode is graphite, and the NP ratio is 1.15. The assembled full battery is subjected to a cycle test after formation. The specific test conditions are as follows: nominal capacity 150mAh / g, electrochemical window 3.4-4.85V, 45°C, 1C cycle 200 times (1C constant current charge to 4.95V, then constant voltage charge to current density 0.05C, and then 1C constant current discharge to 3.5V is one cycle), record the cycle retention rate, and remove the negative electrode sheet after the cycle, and perform ICP-OES test on the negative electrode sheet. The obtained Mn content is the Mn dissolution amount.
[0133] Table 2:
[0134]
[0135]
[0136] It can be seen from Table 2 that, compared with positive electrode active materials D1 and D2, positive electrode active materials C1-C10 are used in batteries, which can significantly reduce the dissolution of manganese and improve the rate performance and cycle stability of the corresponding batteries; further, compared with positive electrode active material D3, positive electrode active materials C11-C13 are used in batteries, which can reduce the dissolution of manganese and significantly improve the rate performance and cycle stability of the corresponding batteries; further, compared with positive electrode active material D4, positive electrode active materials C14-C16 are used in batteries, which can reduce the dissolution of manganese and improve the rate performance and cycle stability of the corresponding batteries; further, compared with positive electrode active material D5, positive electrode active materials C17-C20 are used in batteries, which can reduce the dissolution of manganese and significantly improve the rate performance and cycle stability of the corresponding batteries.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material satisfies the following formula 1: I1+I2+I3≤10.20 Formula 1; Among them, I1 is I(111) / I(311) in the XRD spectrum of the positive electrode active material, I2 is I(111) / I(400) in the XRD spectrum of the positive electrode active material, I3 is I(111) / I(440) in the XRD spectrum of the positive electrode active material, and I1, I2, and I3 are all not 0.
2. The positive electrode active material according to claim 1, characterized in that The XRD spectrum of the positive electrode active material also includes a rock salt phase Li x Ni 1-x The diffraction peak of O.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The chemical composition of the positive electrode active material includes Li 1+x Ni 0.5+y Mn 1.5+z M u N v O w , wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 0<v≤0.03, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F; N includes at least one of Mg, Ca, Co, Ni, Zn, Sr, Y, Sn, Ba, La, Ce, and Nd.
4. The positive electrode active material according to claim 3, characterized in that The positive electrode active material satisfies the following formula 2: 0.0005≤y / x≤0.0100 Formula 2; Wherein, x is the particle size of the positive electrode active material, in μm, and y is the thickness extending from the surface of the positive electrode active material to the core to the point where the N concentration is 0, in μm.
5. The positive electrode active material according to claim 4, characterized in that 0.001μm≤y≤0.02μm; And / or, the Dv50 of the positive electrode active material is 1 to 15 μm.
6. A method for preparing a positive electrode active material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Prepare a first precursor material, wherein the chemical composition of the first precursor material is Li 1+x Ni 0.5+y Mn 1.5+z M u O w , wherein, -0.1≤x≤0.2, -0.1≤y≤0.1, -0.3≤z≤0.3, 0≤u≤0.2, 3.8≤w≤4.3; M includes at least one of Al, Sc, Ti, V, Cr, Fe, Cu, Ga, Sr, Y, Zr, Nb, Mo, Ru, Ta, W, B, Si, Ge, Sb, Te, P, S, and F; 2) mixing the first precursor material with a soluble salt solution of N, stirring, filtering, and drying in sequence to obtain a second precursor material; 3) The second precursor material is sintered at 700-1000° C. to obtain the positive electrode active material.
7. The preparation method according to claim 6, characterized in that: The first precursor material is prepared by a method comprising the following steps: The molecular formula is Ni 0.5 Mn 1.5 The (OH)4 precursor, lithium source and M source are mixed, and the obtained mixture is sintered at 900-1100°C for 5-30h, and then cooled to 600-800°C at a cooling rate of 0.1-3°C / min, and kept warm for 1-10h to obtain the first precursor material.
8. The preparation method according to claim 6, characterized in that: In the N soluble salt solution, the concentration of element N is 0.01-1 mol / L.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer arranged on at least one surface of the current collector; the positive electrode active layer comprises the positive electrode active material according to any one of claims 1-5.
10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Lithium ion battery
CN120999134A
Positive plate, battery, battery pack and electric equipment
CN121416428A
Positive electrode active material and preparation method therefor, positive electrode sheet, and battery
WO2026067606A1